The Accuracy of Equity Valuation using Price-Earnings Multiple for UK Buyouts. - Singh, Samardeep (2011)
Equity valuation using P/E multiples is widely used globally across all investment banks primarily to assist their clients, advising them whether to purchase or sell a business or to raise capital for growing a business. The success of any business deal critically depends on valuation. Accurate valuation, thus, interests most of the analysts/investment bankers. Despite such wide and critical usage there is limited research around the topic. Literature suggests that researchers have estimated the accuracy of this technique but their work is limited to a few markets and some specified intervals of time. The results they come up with should not be generalized to all markets that exist around the globe rather should be empirically tested on other markets as well. With a little empirical evidence on the effectiveness of P/E equity valuation method as far as international equity markets are concerned, this report adds to its empirical evidence for UK buyouts. This report estimates accuracy of valuation using P/E multiple, constructed both with forward and trailing earnings and finds out whether there is any significant difference between the two. Further, the report analyzes how valuation accuracy varies with target firm size. It contributes to the ongoing research on valuation by providing an estimate of P/E valuation technique for UK markets. The results produced are useful for UK investment bankers and practitioners who deal with equity valuations. The results also have implications for further research around the topic.